4E‐BP1 regulates the differentiation of white adipose tissue. (15th May 2013) - Tsukiyama‐Kohara, Kyoko; Katsume, Asao; Kimura, Kazuhiro; Saito, Masayuki; Kohara, Michinori
<x xml:space="preserve">Abstract</x> 4E Binding protein 1 (4E‐BP1) suppresses translation initiation. The absence of 4E‐BP1 drastically reduces the amount of adipose tissue in mice. To address the role of 4E‐BP1 in adipocyte differentiation, we characterized 4E‐BP1−/− mice in this study. The lack of 4E‐BP1 decreased the amount of white adipose tissue and increased the amount of brown adipose tissue. In 4E‐BP1−/− MEF cells, PPARγ coactivator 1 alpha (PGC‐1α) expression increased and exogenous 4E‐BP1 expression suppressed PGC‐1α expression. The level of 4E‐BP1 expression was higher in white adipocytes than in brown adipocytes and showed significantly greater up‐regulation in white adipocytes than in brown adipocytes during preadipocyte differentiation into mature adipocytes. The amount of PGC‐1α was consistently higher in HB cells (a brown preadipocyte cell line) than in HW cells (a white preadipocyte cell line) during differentiation. Moreover, the ectopic over‐expression of 4E‐BP1 suppressed PGC‐1α expression in white adipocytes, but not in brown adipocytes. Thus, the results of our study indicate that 4E‐BP1 may suppress brown adipocyte differentiation and PGC‐1α expression in white adipose tissues.